Experimental Study of the Effect of Condenser Tubes Distribution for Domestic Refrigerator - Mutasher, Dheya Ghanim (Al-Khwarizmi Engineering Journal, 2017)
The performance of a condenser in a domestic refrigerator system without wires and a condenser with a novel design consisted of number of loops as elliptical shape is investigated experimentally in this work. The experiment was conducted with a refrigerator designed to work with HFC134a, under no load and with loads of (1.5,3 and 12 liters of water). In particular, the effects of shape change of the condenser were very important in heat transfer enhancement and reduce of the frictional loss as a result of reducing the pressure drop in the condenser. The results shown that compressor work decreases with elliptical condenser about (8.6% to 11.3%), and then the power consumption decreases also. The performance of household refrigerator with an elliptical condenser without fins was better than that of the conventional condenser without fins. Therefore, the elliptical condenser can be used instead of the conventional air cooled condenser in a domestic refrigeration system.